Development and experimental validation of conceptual models for solenoid-based in-vessel two-channel control rod position indicator - Soonwoo Han; Jae-Seon Lee (Nuclear Engineering and Technology)
In this study, we proposed in-vessel two-channel control rod positioner models for small nuclear reactors and carried out performance tests to evaluate applicability of the models. Embedding control rod positioners in reactors reduces the volume of small reactors and minimizes the penetration parts of reactor. In this study, two models having two physically separated solenoids were developed for measuring the position of the control rod by using the inductance change of a solenoid. First, the principle of measuring the position of a ferromagnetic rod by using a solenoid was formulated, and the change in solenoid inductance with the rod position was calculated through finite element analysis. Based on the proposed models, test products were manufactured and tested on three items to confirm the feasibility of the proposed solenoid-based two-channel control rod position indicator.